Оцінка доцільного рівня цільової надбавки до тарифу на електроенергію існуючих АЕС України для забезпечення виконання робіт із зняття їх з експлуатації - Shulzhenko S.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2013)
The analysis of local legislation and normative acts concerning radiological safety of national NPP and funds formation for decommissioning needs are in the article. The article also presents IAEA methodological recommendations for NPP’s electricity tariff formation that provides enough funds for NPP decommissioning. Appropriate use of the recommendations is proven for Ukrainian NPP in conditions of further integration of national power system with power systems of EC countries.The method of electricity tariff premium formation that could cover financial needs of decommissioning for Ukrainian NPP using IAEA methodological recommendations is suggested. The appropriate level of premium for Ukrainian NPP decommissioning process was calculated taking into account uncertainty of exploitation conditions and amount of funds for removal of them from exploitation.The article proves that suggested approach to cover financial needs of NPP decommissioning allows to minimize potentially essential financial obligations of Ukrainian State Budget and assists sustainable and safe development national nuclear energy.